A 2-base insertion in exon 5 is a common mutation of the TP53 gene in dogs with histiocytic sarcoma - ASADA, Hajime (J Vet Med Sci, 2017)
Canine histiocytic sarcoma (HS) is a malignancy originating from the histiocytic cell lineage and characterized by poor response to chemotherapy and short survival time. Mutation of the TP53 gene and its association with poor prognosis has been reported in several canine tumors. However, the mutation of this gene has not been investigated in canine HS. The aim of this study was to examine a TP53 gene mutation in dogs with HS. Aberrations of the TP53 gene were examined by polymerase chain reaction-single strand conformational polymorphism analysis and DNA sequence analysis, revealing mutations of the TP53 gene in 12 (46%) of 26 dogs affected by HS. The incidence of the TP53 gene mutation was relatively high in canine HS compared with other canine tumors. Among these mutations, 10 of 12 dogs (83%) with a TP53 gene mutation harbored the same mutation: a 2-base (AT) insertion in exon 5, resulting in the introduction of a stop codon (c.446_447insAT, p.Tyr150SerfsX8). Further studies are needed to examine the functional change due to the mutation and its association with the pathogenesis of canine HS.